CORRELATION OF CA 15.3 LEVELS WITH METASTASIS IN BREAST CANCER - KARTHIKHAEYAN TR; ASWIN KARTHIK PERIASAMY; ANKITKUMAR SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective is to measure the serum levels of Cancer Antigen CA 15.3 in breast cancer patients with metastasis and without metastasis and compare the mean values between them. The study investigated the correlation between CA 15.3 levels and metastasis in breast cancer. Methods: The study was conducted with 45 female patients in a tertiary care center in India, and metastatic evaluation was done using positron emission tomography–computed tomography. Results: The results indicated that CA 15.3 levels were significantly higher in the metastatic group compared to the non-metastatic group. Conclusion: CA 15.3 has the potential as a diagnostic tool for early detection of metastases in breast cancer patients.